Optimized ammonium removal using Al-modified bentonite: Insights into structural and mineralogical changes - Hoang-Minh, Thao; Nguyen-Thanh, Lan; Thi Pham, Nga; Van Bui, Dong; Nguyen Thi, Hai; Dinh Nguyen, Thai; Minh Thi Nguyen, Thuyet; Duy Nguyen, Thien; Mählmann, Rafael Ferreiro; Kasbohm, Jörn (Vietnam Journal of Earth Sciences, 2025)
Highly effective adsorbents derived from modified Di Linh bentonite (Lam Dong Province, Vietnam) were produced using Al3+ stock solution prepared from Al2(SO4)3•18H2O. Mineral, morphology, and surface area properties of untreated and Al-modified Di Linh bentonite were characterized using X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscopy, and nitrogen adsorption-desorption analyses. A scanning experiment was conducted to investigate the Al-modified bentonite material’s ammonium (NH₄⁺) removal capacity at two levels of NH₄⁺ initial concentration. Results show that the combination of acid H2SO4 (a bioproduct of diluted Al solution) with Al3+ caused the smectitization of clay particles via a dissolution-precipitation mechanism, which enhances the structural organization of smectite and modifies its mineralogical properties. This process promoted the removal capacity of Al-modified bentonites, which increased to 0.47 mg/g in comparison with 0.32 mg/g from untreated bentonite at 50 mg/L NH4+-N concentration, to 19.3 mg/g in comparison with 17.2 mg/g from untreated bentonite at 1000 mg/L NH4+-N concentration. This approach to modifying natural bentonite offers new possibilities for developing adsorbents to eliminate NH4+ from water.